Quo Vadis Collaborative Learning In Primary Schools: A Systematic Review of Trends, Epistemological Shifts, and Research Gaps - Amri Saputra; Dini Cahyati; Shukri Bin Suparti (Institut Agama Islam Negeri Palopo, 2026)
Research on collaborative learning in primary schools has grown substantially over the past decade, but its epistemological depth and global representation remain uneven. This article maps the developmental trajectory of collaborative learning research in primary schools from 2010 to 2026 and identifies the research gaps that remain open. Based on a systematic review of 198 Scopus-indexed articles following the PRISMA protocol, the analysis identifies five developmental phases that reflect shifts in epistemological focus rather than chronology alone: the exploration of dialogic technology (2010–2014), the structuring of cooperative models (2015–2019), pandemic-driven disruption and digitalization (2020–2022), the integration of social-emotional and artificial intelligence approaches (2023–2024), and an emerging orientation toward inclusivity and sustainability (2025–2026). The analysis further identifies three clusters of structural gaps: theoretical (the dominance of Western frameworks and the scarcity of locally grounded models), methodological (the predominance of short-term designs and limited analysis of interaction processes), and practical (the absence of cost-effectiveness studies and limited research in marginalized school contexts). In the Indonesian context, the most salient gap is the absence of a collaborative learning model that systematically incorporates the value of gotong royong (communal mutual assistance) as a pedagogical foundation. This gap suggests a concrete direction for future theory-building and empirical validation in Southeast Asia.